Los 'Trionfi' de Petrarca comentados en catalán: una edicion de los manuscriptos 534 de la biblioteca nacional de Paris y del Ateneu de Barcelona / por Roxana Recio - Recio, Roxana, 1953- (Chapel Hill : University of North Carolina at Chapel Hill Department of Romance Studies, 2009)
This is the first complete edition of an anonymous late medieval Catalan translation of Italian writer Bernardo Illicino's commentary on Petrarch'sTriumphs. Although the translation of Illicino's commentary is considered a classic of Catalan prose by scholars, until now, no one has undertaken the task of preparing a complete edition because of the complexity of the prose, and because the original manuscript survives in two pieces in two different libraries: the National Library of France in Paris and the Ateneu in Barcelona. The original document, reproduced here, represented the first attempt to introduce Petrarch'sTriumphsto Peninsular readers and constituted an essential document for the study of the introduction and development of Iberian Petrarchism. This translation of theTriumphsis different from later renditions by the order and content of its chapters.The introduction to this volume raises interesting questions about the translation's nature and about the readers for which it was intended, while underscoring the fact that Italian Humanism was introduced in the Iberian Peninsula through the Catalan-speaking intellectuals in the Aragonese Crown. Written in Spanish with Petrach's verses preserved in the original Italian.
JSTOR
Keywords: Petrarca, Francesco, -- 1304-1374.; Petrarca, Francesco, -- 1304-1374 -- Translations into Catalan -- History and criticism; Petrarca, Francesco, -- 1304-1374; Trionfi (Petrarca, Francesco); Criticism, interpretation, etc